2012
DOI: 10.1007/s11192-012-0908-1
|View full text |Cite
|
Sign up to set email alerts
|

A ‘perverse incentive’ from bibliometrics: could National Research Assessment Exercises (NRAEs) restrict literature availability for nature conservation?

Abstract: Recovery plans in all countries also contained 37 % or more citations to 'grey literature', discounted in NRAEs. If NRAEs discourage peer-reviewed publication at any level they could exacerbate the trend not to publish information useful for applied conservation, possibly harming conservation efforts. While indicating the potential for an impact does not establish that it occurs, it does suggest preventive steps. NRAEs considering the proportion of papers in top journals may discourage publication in lower-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
(65 reference statements)
1
11
0
3
Order By: Relevance
“…These findings reflect recent calls in the literature for a revolution in research assessment, highlighting the need to build a collaborative infrastructure between funding sources, research institutions and practitioners (e.g. Largent and Lane 2012;Calver et al 2013). Until institutions rethink the criteria by which they measure success and allocate funding, they will continue to reinforce mismatches between research and practice.…”
Section: Bridging the Gap -What Now?supporting
confidence: 73%
“…These findings reflect recent calls in the literature for a revolution in research assessment, highlighting the need to build a collaborative infrastructure between funding sources, research institutions and practitioners (e.g. Largent and Lane 2012;Calver et al 2013). Until institutions rethink the criteria by which they measure success and allocate funding, they will continue to reinforce mismatches between research and practice.…”
Section: Bridging the Gap -What Now?supporting
confidence: 73%
“…Nevertheless, these studies would enlighten efforts to conserve Australian native mammals, and need to be recognised for their important contribution (Calver et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of specific aspects of a threatened species' biology are most likely to influence how we manage the recovery or conservation of that species; however, such studies are likely to be turned away by the editorial boards of the highest impact international journals as being parochial and of limited interest. Nevertheless, these studies would enlighten efforts to conserve Australian native mammals, and need to be recognised for their important contribution (Calver et al 2013b).…”
Section: Should We Be Talking About Research Effort or Research Impact?mentioning
confidence: 99%
“…Limited research on these topics in the field of biological conservation identified poor coverage of relevant regional or non-journal literature in some databases (Stergiou and Tsikliras, 2006;Calver et al, 2011Calver et al, , 2013a, and incomplete research profiles for individual researchers if only one database is used for assessment (Calver et al, 2013c).…”
Section: Introductionmentioning
confidence: 99%